Sex Analysis of Lipid Profile in Diabetes Patients with and without Over Weight in Tikrit City/Iraq - Mohammed, Asmaa Sultan; Salih, Maan Hasan; Mahmoud Al-Doori, Maksood Adil (Journal for Research in Applied Sciences and Biotechnology, 2022)
Background: The overweight is one of the main reasons for the development of diabetes, so the lipid profile is different between the diabetes and the healthy people. In addition, there is a variation between the lipids profile according to sex difference in the diabetes patients. The main goal of the current study was to assessment the relationship between lipid profiles-based sex difference of diabetes patients (with and without overweight) and control group. Methodology: In this study, the glucose level and lipid profiles were determined for one hundred and forty volunteers, thirty-nine of them were healthy as a control group (25 females and 16 males), and one hundred and two had diabetes, 50 diabetes with overweight (25 females and 25 males) and 52 diabetes without overweight (27 females and 25 males). Results: Concerning the results of glucose level, the results of the current study showed significant differences between males and females in HbA1c test of control group (P=0.024) and in PPG test of Diabetes without overweight group (P=0.033). On other hands, our results found variation between men and women in other groups but not reach to significant differences. While the results of lipids profile showed significant differences between males and females in HDL_C test of diabetes without overweight group (P=0.0246) and in LDL_C test of control group (P=0.02). At the same time, our results recorded variation between men and women in other groups but not reach to significant differences. Conclusions: The research presents important results on the differences between sex and its content of lipid profiles in diabetic patients, although some differences did not reach at significant level, but they showed clear sex differences.